Manajemen Dana Wakaf Dalam Pengembangan Pariwisata Halal di Bayt Al-Qur'an Al - Akbar Gandus Palembang - Dita Faradila; Muhammadinah Muhammadinah; Mahmud Alfan Jamil (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2022)
Abstract: The Potensial for artifical tourism which is one of the great economic development magnetis in the city of Palembang can increase regional income assets. Halal tourism Bayt Al-Qur'an Al-Akbar Gandus Palembang is an example of halal tourism object, one of waqf funds in the development of halal tourism in Bayt Al-Qur'an Al-Akbar Gandus Palembang. The results showed that it was in accordance with the management function based on the POAC function (Planing, Organizing, Actuating and Controling). However, it related to people who are waqf where there is a need for a desaign related to people who are waqf other than the waqf pledge.